Association between area-level material deprivation and incidence of hospitalization among children with SARS-CoV-2 in Montreal. (23rd April 2022) - Abda, Assil; del Giorgio, Francesca; Gauvin, Lise; Autmizguine, Julie; Kakkar, Fatima; Drouin, Olivier
Abstract: Background: Although sociodemographic factors have been linked with SARS-CoV-2 infection and hospitalizations in adults, there are little data on the association between sociodemographic characteristics and SARS-CoV-2-related hospitalization in children. The objective of this study was to determine the association between area-level material deprivation and incidence of hospitalization with SARS-CoV-2 among children. Methods: We conducted a retrospective cohort study of all children (0 to 17 years of age) with a PCR-confirmed SARS-CoV-2 infection March 1, 2020 through May 31, 2021 at a tertiary-care paediatric hospital, in Montreal, Canada. Data were collected through chart review and included age, sex, and postal code, allowing linkage to dissemination area-level material deprivation, measured with the Pampalon Material Deprivation Index (PMDI) quintiles. We examined the association between PMDI quintiles and hospitalization using Poisson regression. Results: During the study period, 964 children had a positive PCR-confirmed SARS-CoV-2 test and 124 were hospitalized. Children living in the most deprived quintile of PMDI represented 40.7% of hospitalizations. Incidence rate ratio of hospitalization for this group compared to the most privileged quintile was 2.42 (95%CI: 1.33; 4.41). Conclusion: Children living in the most materially deprived areas had more than twice the rate of hospitalizations for COVID-19 than children living in most privileged areas. Special efforts should be deployed to protect children who live in disadvantaged areas, especially pending vaccination of younger children.